Palmitic acid induces GSDMD‐mediated pyroptosis in periodontal ligament cells via the NF‐κB pathway - Sun, Bing‐Jing; Chen, Mei‐Hua; Zhang, Wei‐Hua; Zhao, Bing‐Jiao; Zhang, Meng‐Han; Han, Xin‐Xin; Yu, Li‐Ming; Liu, Yue‐Hua (Oral diseases, 2024)
Objective Obesity can affect periodontal tissues and exacerbate periodontitis. Pyroptosis, a newly identified type of inflammatory cell death, is involved in the development of periodontal inflammation. The saturated fatty acid palmitic acid (PA) is elevated in obese patients. The effect of PA on pyroptosis in periodontal ligament cells (PDLCs) and its underlying mechanisms remain unknown. Materials and Methods Human PDLCs were isolated from healthy individuals and cultured for experiments. The effects of PA on PDLC pyroptosis and the underlying mechanisms were examined by transmission electron microscopy, quantitative real‐time PCR and western blotting. Results The morphology of PDLCs in the PA group indicated pyroptotic characteristics, including swollen cells, plasma membrane rupture and changes in subcellular organelles. PA induced inflammatory responses in PDLCs, as indicated by an increase in IL‐1β in the cell culture supernatant. Furthermore, we found that the pyroptosis‐related proteins caspase‐1, caspase‐4 and GSDMD were involved in PA‐induced cell death. GSDMD and caspase‐4 inhibitors alleviated pyroptotic death of PDLCs. Moreover, PA promoted NF‐κB P65 phosphorylation. A NF‐κB inhibitor decreased IL‐1β expression and partly rescued cell death induced by PA. Conclusion PA activated the NF‐κB pathway and induced the inflammatory response in PDLCs. Caspase‐4/GSDMD mediated PDLC pyroptosis induced by PA.